2016
DOI: 10.1111/faam.12081
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Accountability During Performance Audits Under Pressure: A Recipe for Institutional Hypocrisy?

Abstract: This study shows how the tensions between transparency and secrecy are likely to engender ‘institutional hypocrisy’ in the accountability process taking place during Supreme Audit Institutions’ performance audits. The examination of relations between the French Cour des comptes, Administration and Parliament has revealed gaps between Administration and Parliamentarians’ discourse and action, secrets and things left unsaid. This impression of Administration and Parliamentarians’ full participation in this democ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
2
23
0
2
Order By: Relevance
“…Blume & Voigt (2011), on the other hand, found that the judicial reports are not presented to the legislative body and not disclosed to the public in judicial type SAIs. Morin (2016) observed in the French example that SAI's audit reports created a false sense of transparency and that citizens were given a false sense of trust that the accounts were actually audited.…”
Section: Th Eoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Blume & Voigt (2011), on the other hand, found that the judicial reports are not presented to the legislative body and not disclosed to the public in judicial type SAIs. Morin (2016) observed in the French example that SAI's audit reports created a false sense of transparency and that citizens were given a false sense of trust that the accounts were actually audited.…”
Section: Th Eoretical Framework and Literature Reviewmentioning
confidence: 99%
“…These results are not reflected in research on the Estonian SAI, however, where the auditees did not perceive performance audit reports as useful (Raudla et al, 2015). And Morin’s recent qualitative research similarly indicated that the impact of the French SAI is weak, its audits contributing more to window dressing than to real influence (Morin, 2016). In the Danish context, Justesen and Skærbek (2010) looked into how accountability mechanisms contributed to the impact of audits, suggesting that they represent forceful mechanisms that induce organizations to implement change.…”
Section: Research On the Impact Of Performance Auditingmentioning
confidence: 99%
“…In later qualitative studies, she problematizes the double role played by auditors as both controllers and management consultants. She also discusses the challenges faced by audit institutions in adopting new evaluation methodologies in performance audits (Morin, 2010, 2016). In a qualitative study, Alwardat (2010) suggests that the utility of performance audits – as perceived by the auditees – depends on their expectations, their view of the auditors’ expertise, the materiality of the auditors’ findings, and the truth and fairness of the reports.…”
Section: Research On the Impact Of Performance Auditingmentioning
confidence: 99%
“…Os estudos existentes sobre independência de organizações de auditória no setor público dividem-se entre os que exploram a influência do poder Executivo sobre as organizações responsáveis por fazer sua auditora (Funnel, 1994;Radcliffe, 1997;Morin, 2010;Seyfried, 2016), e aqueles relacionados ao duplo papel exercido pelas organizações de auditoria -que além de fiscalizar também atuam como promotores de melhores práticas 5 (Gendron, Cooper & Townley, 2001;Morin, 2016;Triantafillou, 2017;Pierre & Licht, 2019).…”
Section: Independência E Lógicas Institucionais Nos Tribunais De Contasunclassified
“…No setor privado, estudos focaram nos impactos da crise de auditoria fruto do caso Arthur Andersen ou na emergente lógica comercial fruto de serviços de consultoria prestados pelas grandes empresas de auditoria, atualmente conhecidas como big four (ver Gendron & Spira, 2009;Suddaby, Gendron & Lam, 2009;Spence & Carter, 2014). No setor público, a discussão também gira em torno do "duplo papel" exercido pelas organizações de auditoriaque atuam coercitivamente como fiscalizadoras, mas também promovem, pedagogicamente, boas práticas (ver Pierre & Licht, 2019;Triantafillou, 2017;Morin, 2016;Gendron et al, 2001).…”
Section: Introductionunclassified